Cost and Productivity Effects of Firm Financed Training - Eugenia Kazamaki Ottersten; Thomas Lindh; Erik Mellander (The Research Institute of Industrial Economics (IUI), 1996)
A quality-adjusted specification of labor is suggested which allows firm training to affect labor efficiency. To assess the cost and productivity effects, this specification is integrated into a flexible neoclassical cost function. The empirical analysis uses panel data for eight plants in the Swedish Machine Tool Industry. The econometric results imply a high probability that training expenditures result in net decreases in total costs. Judging from the corresponding point estimates, these cost savings can be very large. The estimates of productivity effects are also positive, albeit rather small.
Keywords: C51; D21; J24; J31; 330; ENTERPRISES; TRAINING; WORKERS; PRODUCTIVITY; Personalentwicklung; Arbeitsproduktivität; Produktionskosten; Werkzeugmaschine; Theorie; Schweden